Carbon Accounting in Practice: Determinants of Emission Disclosure among Indonesian Non-Financial Firms - Ni Luh Putu Pebri Anggreni; I Gusti Ayu Nyoman Budiasih (E-Jurnal Akuntansi, 2026)
This study investigates whether industry type, media exposure, and environmental performance influence carbon-emission disclosure by non-financial firms listed on the Indonesia Stock Exchange during 2022–2023. The sample comprises 178 annual and sustainability reports issued over the two-year period. Carbon-emission disclosure, the dependent variable, is measured through content analysis, whereas industry type, media exposure, and environmental performance serve as the explanatory variables. Legitimacy theory provides the interpretive lens. Multiple-linear-regression analysis, performed with SPSS 25, reveals that industry type does not affect the extent of carbon-emission disclosure. By contrast, both media exposure and environmental performance exert positive, significant effects. Firms that receive carbon-related media coverage and demonstrate strong environmental performance appear more willing to disclose strategic actions aimed at managing their environmental impact.